Oncology Nursing in Singapore: How It Evolved and What Does the Future Hold? - Gek Phin Chua (Elsevier, 2020)
Cancer is the leading cause of death in Singapore since the early 1980s and has remained so since then, accounting for 29.7% of deaths in 2015. Rapid technological advancements in the treatment of cancer and the development of the specialty of radiation and medical oncology demanded nurses with the knowledge and skills to provide care and support to cancer patients and their families. The evolvement of oncology nursing as a specialty in Singapore mirrors many countries due to the increase in cancer incidences as well as the development of medical specialty in the treatment of cancer. This paper traces the development of oncology nursing as a clinical specialty in Singapore. The historical perspective maps up the factors that caused oncology nursing to develop as a specialty within nursing practice. As cancer continues to be the leading cause of mortality for many years to come in Singapore and cancer care continues to evolve, the roles of oncology nurses will continue to unfold and expand as part of an interdisciplinary team in the fight against cancer.